Identification and Characterization of Novel Compounds Blocking Shiga Toxin Expression in Escherichia coli O157:H7 - Huerta-Uribe, Alejandro; Marjenberg, Zoe R.; Yamaguchi, Nao; Fitzgerald, Stephen; Connolly, James P. R.; Carpena, Nuria; Uvell, Hanna; Douce, Gillian; Elofsson, Michael; Byron, Olwyn; Marquez, Rudi; Gally, David L.; et al. (Frontiers in Microbiology, 2016)
Infections caused by Shiga toxin-producing E. coli strains constitute a health problem, as they are problematic to treat. Shiga toxin (Stx) production is a key virulence factor associated with the pathogenicity of enterohaemorrhagic E. coli (EHEC) and can result in the development of haemolytic uremic syndrome in infected patients. The genes encoding Stx are located on temperate lysogenic phages integrated into the bacterial chromosome and expression of the toxin is generally coupled to phage induction through the SOS response. We aimed to find new compounds capable of blocking expression of Stx type 2 (Stx2) as this subtype of Stx is more strongly associated with human disease. High-throughput screening of a small-molecule library identified a lead compound that reduced Stx2 expression in a dose-dependent manner. We show that the optimised compound interferes with the SOS response by directly affecting the activity and oligomerisation of RecA, thus limiting phage activation and Stx2 expression. Our work suggests that RecA is highly susceptible to inhibition and that targeting this protein is a viable approach to limiting production of Stx2 by EHEC. This type of approach has the potential to limit production and transfer of other phage induced and transduced determinants.